(3CSQGQ GdJQhjL aj YUQ GdYhdeI (B:s (3JLGQH TQcGJ OhdjI aj GdJQhjL (B/s - (3YHO GdUHhQ, eMSf aJMis ((3GdbGgQI(B: s (3eLehYI Gdfjd GdYQHjI(B, s, 2001)
(3CSGSjGJ GdJQhjL;GdeYGQV GdJLGQjI,eWHhYGJ GdJQhjL,RjGQI GdCShGb GdNGQLjI,GdOYGjI hGdEYdGf,GdJQhjL YHQ THcI GdCfJQfJ,JfTjW GdeHjYGJ,GdJQhjL GdeHGTQ,Jbhje HQGeL GdJQhjL,JLGQH TQcGJ OhdjI,CSQGQ fLGM GdjHGfjjf aj GdJQhjL,GdJQhjL aj GdbQf GdhGMO hGdYTQjfs
(3GdedGMb U(B.155 (3HHdjhZQGajG(B: (3U(B.167s
Keywords: (3GdJShjbs